Migration, Risk Attitudes, and Entrepreneurship: Evidence from a Representative Immigrant Survey - Catia Batista; Janis Umblijs (Institute for the Study of Labor (IZA), 2013)
Do more risk loving migrants opt for self-employment? This is a question especially relevant for policymakers designing selective immigration policies in countries of destination. In order to provide a rigorous answer to it, we use a novel vignette-adjusted measure of risk preferences in the domain of work to investigate the link between risk aversion and entrepreneurship in migrant communities. Using a representative household survey of the migrant population in the Greater Dublin Area, we find a significant negative relationship between risk aversion and entrepreneurship. In addition, our results show that the use of vignettes improves the significance of the results, as they correct for differential item functioning (where respondents interpret the self-evaluation scale in different ways) between entrepreneurs and non-entrepreneurs, and corrects for variation in the use of self-evaluation scales between migrants from different countries of origin.
Keywords: F22; J01; J15; J61; L26; 330; migration; risk aversion; entrepreneurship